Can extracellular vesicles from bovine ovarian follicular fluid modulate the in-vitro oocyte meiosis progression similarly to the CNP-NPR2 system? - Pioltine, Elisa M. [UNESP]; Machado, Mariana F. [UNESP]; da Silveira, Juliano C.; Fontes, Patrícia K. [UNESP]; Botigelli, Ramon C. [UNESP]; Quaglio, Ana Elisa V. [UNESP]; Costa, Camila B. [UNESP]; Nogueira, Marcelo F.G. [UNESP] (Elsevier, 2020)
C-type natriuretic peptide (CNP) and its natriuretic peptide receptors subtype 2 (NPR2) are essential for the maintenance of oocyte meiotic arrest in different species. Extracellular vesicles (EVs) in bovine follicular fluid (FF) are important for cell communication within the ovarian follicle. This study investigated the involvement of EVs from FF of bovine ovarian follicles in the CNP-NPR2 system, first by analyzing the presence of CNP in the EV contents, followed by addition of EVs to in-vitro maturation (IVM) medium, to evaluate the effect on maintenance of oocyte meiosis arrest and improvements in in-vitro embryo production. As expected, CNP was observed in FF and granulosa cells from the ovarian follicles. To the best of our knowledge, this is the first time that CNP has been found in the EV contents. To evaluate the possible effect of EVs on the progression of oocyte meiosis, the IVM was performed under three conditions: CNP and EV supplementation and control condition. Both the CNP and EV treatments inhibited meiosis resumption in the oocyte within 9 h of IVM. CNP treatment increased cGMP levels in cumulus cells within 6 h of IVM compared to the control group, but the EV treatment did not. In contrast, the relative mRNA abundance of adenylate cyclase 3 and 9 (ADCY3 and ADCY9) was upregulated in oocytes after 6 h of IVM under EV treatment compared to the control group, but not under CNP treatment. Last, these treatments in the IVM medium had no significant effect on the in-vitro embryo production. In conclusion, we demonstrated the presence of endogenous CNP in bovine reproductive structures, especially in the EVs from the FF of antral follicles. The presence of CNP in the EVs suggests an important involvement of this cell-communication system in the CNP-NPR2 system. Therefore, we indeed observed that the EVs from FF can modulate the arrest of oocyte meiosis, acting similarly to the CNP-NPR2 system to block the oocyte in the GV state. However, the mechanism of each system might be different; the CNP-NPR2 system seems to be involved in modulating the cGMP levels, while the contents of EVs might be involved in modulating the cAMP levels.
Keywords: Bovine; CNP; Extracellular vesicles; Meiotic arrest